PENDAMPINGAN PEMANFAATAN MEDIA SOSIAL SEBAGAI SARANA PENGEMBANGAN POTENSI DESA BINAAN DI DESA SEMBAWA KUNINGAN JAWA BARAT - Ratih Kurnia Hidayati; Edison Hatoguan Manurung; Fitriana Sandi; Josua Fernando; Serepina Tiurmaida; Bambang Rismadi (Indonesian Collaboration Journal of Community Services, 2022)
Sembawa Village located in Kuningan, West Java holds one village potential. The condition of road access to a good village becomes interesting if the village community independently wants to manage the potential in the village. Independent community service activities in collaboration with KKN students develop this potential into their thematic programs. The method of application in the form of assistance and external results in the form of Websites and Social Media Accounts is expected that the public will begin to open their eyes to develop this potential. From the results of the assistance evaluation, it is needed for the participation of extension participants, especially the local government, to be able to manage the potential. The team expects this activity to grow their motivation to be selective and active in the media. The intelligent and critical attitude in the growing media makes them village youths become a virus for their friends who have not participated in the promotion. They hope that activities can be carried out sustainably, considering that it is not only education but also entertainment and motivation in building the country by utilizing the potential around them